Transformasi pembelajaran berdiferensiasi pada pembelajaran pendidikan pancasila: memaknai aturan di sekolah - Erina Dewi Fatmasari; Charunia Putri Banowati; Arini Arini; Deni Zein Tarsidi (Didaktika Dwija Indria, 2025)
The application of the Contextual Teaching and Learning (CTL) model in Pancasila education learning in elementary schools had not been able to accommodate various learning styles of students, especially students with kinesthetic learning tendencies. This indicated the need for alternative solutions in the application of the CTL model. This study used a case study approach with observation data collection techniques and literature reviews. The results of the study indicated that the CTL model was less effective in meeting the needs of kinesthetic students who required movement and physical interaction. Therefore, this study emphasized the need to develop a differentiated learning approach that could accommodate various learning styles, with adjustments to the content, process, and learning outcomes. This approach was expected to increase student motivation, engagement, and understanding, while creating a more inclusive and relevant learning experience for all students.